Understanding the effects of physical properties of composite drop on its formation dynamics in presence of interfacial mass transfer - Khan, Muzammilanwar S.; Kulkarni, Amol A. (Industrial and Engineering Chemistry Research, 2024)
Dynamics of drop formation is studied in presence of interfacial mass transfer through controlled flow visualization experiments and lumped force balance based model. Experiments were conducted using eight different combinations of ternary systems, involving variations in initial composition and physical properties of drop phase over a broad range. A new image analysis method is reported to accurately measure the size of deformed, nonaxisymmetric drops. Based on flow visualization and analysis of drop shape, four modes of drop formation are identified, including (i) mass transfer free mode, (ii) interfacial instability mode (Marangoni effects), (iii) dripping, and (iv) jetting, with progressively increasing solute concentrations. Exceptions to these modes are observed for tetrahydrofuran-toluene and tetrahydrofuran-benzene mixtures, in which the drop remains in mass transfer free mode even in presence of higher solute concentrations. Model predictions of real time change in drop volume show excellent match with experimental results for all of the systems under study. The analysis of force balance implies that the interplay between (i) surface tension force and (ii) the combination of buoyancy and force due to kinetic energy controls the drop detachment time as well as the final drop volume. Therefore, for identical operating conditions, transition in drop formation time occurs from 4 s to 65 ms, depending on the density difference and interfacial tension between contacting phases. The present findings provide detailed insights into the formation dynamics of composite drops, which are commonly encountered in liquid-liquid extraction and various multiphase operations.